Induction of MHC class I molecule cell surface expression and epigenetic activation of antigen-processing machinery components in a murine model for human papilloma virus 16-associated tumours - Manning, Jasper; Indrova, Marie; Lubyova, Barbora; Pribylova, Hana; Bieblova, Jana; Hejnar, Jiri; Simova, Jana; Jandlova, Tana; Bubenik, Jan; Reinis, Milan (Immunology, 2008)
Epigenetic events play an important role in tumour progression and also contribute to escape of the tumour from immune surveillance. In this study, we investigated the up-regulation of major histocompatibility complex (MHC) class I surface expression on tumour cells by epigenetic mechanisms using a murine tumour cell line expressing human E6 and E7 human papilloma virus 16 (HPV16) oncogenes and deficient in MHC class I expression, as a result of impaired antigen-presenting machinery (APM). Treatment of the cells with the histone deacetylase inhibitor Trichostatin A, either alone or in combination with the DNA demethylating agent 5-azacytidine, induced surface re-expression of MHC class I molecules. Consequently, the treated cells became susceptible to lysis by specific cytotoxic T lymphocytes. Further analysis revealed that epigenetic induction of MHC class I surface expression was associated with the up-regulation of APM genes [transporter associated with antigen processing 1 (TAP-1), TAP-2, low-molecular-mass protein 2 (LMP-2) and LMP-7]. The results demonstrate that expression of the genes involved in APM are modulated by epigenetic mechanisms and suggest that agents modifying DNA methylation and/or histone acetylation have the potential to change the effectiveness of antitumour immune responses and therapeutically may have an impact on immunological output.
Keywords: Animals; apoptóza; Papillomavirus Infections; geny MHC třídy I; lidský papilomavirus 16; azacytidin; Apoptosis; Up-Regulation; prezentace antigenu; Enzyme Inhibitors; lidé; Mice; upregulace; Genes, MHC Class I; Azacitidine; nádorové buňky kultivované; polymerázová řetězová reakce s reverzní transkripcí; Hydroxamic Acids; experimentální nádory; myši; kyseliny hydroxamové; epigeneze genetická; Tumor Cells, Cultured; Reverse Transcriptase Polymerase Chain Reaction; inhibitory enzymů; infekce papilomavirem; histony; Histones; Human papillomavirus 16; zvířata; Mice, Inbred C57BL; Antigen Presentation; Neoplasms, Experimental; Epigenesis, Genetic; myši inbrední C57BL; Humans